A Suggested Approach of Managing Excessive Maxillary Gingival Display in Terminal Dentition. (20th November 2020) - Saad, Daniel; Moukarzel, Celine; Haddad, Naim El; Rizk, Anthony
Abstract : The aim of this paper is to report a suggested approach for the management of excessive maxillary gingival display with terminal dentition. A segmental osteotomy of the maxillary process was performed, and the latter used as grafting material for lateral sinus augmentation that was performed simultaneously. Following the graft maturation period, implants were inserted and rehabilitated with a fixed dentogingival prosthesis. Consequently, the mandible was prosthetically restored following the new occlusal plane dictated by the rehabilitated maxilla. Clinically, the procedure showed a drastic improvement in the patient's appearance, eliminating the excessive gingival display. Radiologically, it led to a vertical translation of the maxillary process level in an apical direction. Nevertheless, the resected process used as grafting material was noticed to have a suboptimal behavior as long as it showed increased intrasinusal resorption, barely sufficient for a regular implant accommodation. The described therapy concept seems to be a plausible approach when it comes to manage excessive maxillary gingival displays in edentulous patients or those presenting a terminal dentition. However, at the time of sinus augmentation, authors recommend to graft a mixture of resected maxillary process and a bone substitute material, in order to get more stable results.